(untitled) (International Journal of Engineering and Computer Science, 2018)
Vehicular Ad Hoc Network (VANET) is the subpart of the Mobile Ad Hoc Network(MANET) that aims at enhancing the safety and efficiency of transportation systems. In VANET vehicles communicate with each other and with roadside units (RSUs). Service oriented vehicular networks are special types of VANETs that provides infrastructure based commercial services, including Internet access, real-time traffic management, video streaming, and content distribution. Many forms of attacks against service-oriented VANETs that attempt to threaten their security have emerged. The success of data acquisition and delivery systems depends on their ability to defend against the different types of security and privacy attacks that exist in service-oriented VANETs. Service-oriented vehicular security system allows VANET users to exploit RSUs in obtaining various types of data. When multiple users are connected to an RSU at a time it may results in RSU network overhead. So a scalable and an efficient system has been designed by applying certain scheduling algorithms there by avoiding Packet delay and traffic overhead.